Introducing English in Preschool Through Developmentally Appropriate Practice (DAP) - Anis Setiyanti (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2021)
This research is aimed to provide a detailed understanding of the implementation of Developmentally Appropriate Practice (DAP) in English teaching at TK Islam Amalina South Tangerang. A qualitative analysis using the ethnography approach was used in the study. The data were gathered through observation, interview, and document review. Research indicates that the objective of the teaching and the method of teaching activities are both consistent with DAP best practices. However, some are not in agreement with the DAP. Furthermore, the topic of discussion was inconsistency. According to the findings of the study, the English teaching at TK Islam Amalina should (1) integrate the child development, subject matters, and language skills, (2) engage children in learning through play, and (3) involve children in learning by doing.